C-Reactive Protein as a Marker of Postoperative Complication of Emergency Colorectal Surgery - Nadal,Luis R M (2021)
Abstract Introduction The literature converges regarding the use of C-reactive protein (CRP) tests between postoperative days (PODs) 3 and 5 of elective procedures. In this period, they have great sensitivity and negative predictive value (NPV) for severe and anastomotic complications about two days before the first clinical sign. The few studies on colorectal urgency suggest that, despite the different initial values according to the surgical indication, following POD 3, the level of CRP is similar to that of elective procedures. However, given the heterogeneity of the studies, there is no consensus on the cutoff values for this use. Objective To validate the use and propose a PO CRP cut-off value in urgent colorectal procedures as an exclusion criterion for complications of anastomosis or the abdominal cavity. Method Retrospective analysis of the medical records of 308 patients who underwent urgent colorectal surgical procedures between January 2017 andDecember 2019. The following data were considered: age, gender, surgical indication, type of procedure performed, complications, CRP levels preoperatively and from POD 1 to 4, and the severity of the complications. We compared the CRP levels and the percentage variations between the preoperative period and PODs 1 to 4 as markers of severe complications using the receiver operating characteristic (ROC) curve. Results The levels of CRP on POD4, and their percentage drops between PODs 2 to 4 and PODs 3 to 4, were better to predict severe complications. A cutoff of 7.45mg/dL on POD 4 had 91.7% of sensitivity and NPV. A 50% drop between PODs 3 and 4 had 100% of sensitivity and NPV. Conclusion Determining the level of CRP is useful to exclude severe complications, and it could be a criterion for hospital discharge in POD 4 of emergency colorectal surgery.